Functional and muscle morphometric effects of ACL reconstruction. A prospective CT study with 1 year follow‐up. Issue 4 (23rd November 2011) - Lindström, M.; Strandberg, S.; Wredmark, T.; Felländer‐Tsai, L.; Henriksson, M.
Abstract : Computed tomography (CT) was used to explore if changes in muscle cross‐sectional area and quality after anterior cruciate ligament (ACL) injury and reconstruction would be related to knee function. Fourteen females and 23 males (16–54 years) underwent clinical tests, subjective questionnaires, and CT 1 week before and 1 year after ACL surgery with semitendinosus‐gracilis (STG) graft and rehabilitation. Postoperatively, knee laxity was decreased and functional knee measures and subjective patient scores improved. The most obvious remaining deficit was the quadriceps atrophy, which was significantly larger if the right leg was injured. Right‐leg injury also tended to cause larger compensatory hypertrophy of the combined knee flexor and tibial internal rotator muscles (preoperatively). The quadriceps atrophy was significantly correlated with the scores and functional tests, the latter also being related to the remaining size of the gracilis muscle. Biceps femoris hypertrophy and, in males only, semimembranosus hypertrophy was observed following the ACL reconstruction. The lack of semimembranosus hypertrophy in the women could, via tibial internal rotation torque deficit, contribute to the less favorable functional and subjective outcome recorded for the women. The results indicate that the quadriceps, the combined knee flexor/tibial internal rotator muscles, side of ACL injury, and sex are important to consider in rehabilitation after STG graft.